2013
DOI: 10.1007/s11999-013-2813-1
|View full text |Cite
|
Sign up to set email alerts
|

CORR Insights: Orthopaedic Residency Applications Increase After Implementation of 80-hour Workweek

Abstract: This CORR Insights TM is a commentary on the article ''Orthopaedic Residency Applications Increase After Implementation of 80-hour Workweek'' by Anakwenze et al. available at DOI 10.1007/s11999-013-2785-1. Where Are We Now?There has been much interest in the effects of the 80-hour workweek on resident performance, lifestyle, and education. As Anakwenze et al. note in this article, there have been conflicting data and opinions regarding whether the work-hour restrictions have achieved their intended results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…The highly competitive nature of the orthopedic surgery application process and the perceived need to interview at 12 programs or more to have a >90% chance to successfully match have presumably contributed to the increasing number of applications submitted. In addition, other studies have suggested that the implementation of the 80-hour work restriction has led to an increase in applications ( 8 , 9 ). The NRMP and others have previously reported on factors such as class rank, USMLE 1 scores, and the number of publications that correlate with a successful match.…”
mentioning
confidence: 99%
“…The highly competitive nature of the orthopedic surgery application process and the perceived need to interview at 12 programs or more to have a >90% chance to successfully match have presumably contributed to the increasing number of applications submitted. In addition, other studies have suggested that the implementation of the 80-hour work restriction has led to an increase in applications ( 8 , 9 ). The NRMP and others have previously reported on factors such as class rank, USMLE 1 scores, and the number of publications that correlate with a successful match.…”
mentioning
confidence: 99%